Woodland caribou management in Alberta: historical perspectives and future opportunities - Elston H. Dzus; Pat Cabezas (Rangifer, 2007)
Woodland caribou conservation has been the topic of much debate for the past few decades. By the late 1970s there was growing concern about declining woodland caribou populations and the interaction between industrial activities and woodland caribou. Initial concerns led to the closure of the licensed hunting season in 1981. Early confrontation between government and industry in the late 1980s transformed into a series of evolving collaborative ventures. Improving our understanding of the basic ecology of woodland caribou in Alberta was at the center of early research efforts; more recent studies have examined the effects of industrial activities on caribou and effectiveness of various mitigation factors. Despite having amassed an impressive body of information from a research and monitoring perspective, progress on implementing effective management actions has been less dramatic. Industry has endured significant costs implementing a variety of perceived conservation initiatives, but caribou populations continued to decline through the last few decades. While some parties feel more research is needed, there is growing consensus that changes to habitat as induced by human activities are important factors influencing current caribou declines. Predation is a proximate cause of most caribou mortality. Climate change mediated alterations to habitat and predator-prey interactions remain a key source of uncertainty relative to future caribou population trends. Management actions will need to deal with long term habitat changes associated with human land use and short term implications of increased predation. In 2005, the provincial minister responsible for caribou conservation responded to the draft 2004 recovery plan and created the Alberta Caribou Committee (ACC). The goal of the ACC is to maintain and recover woodland caribou in Alberta’s forest ecosystems while providing opportunities for resource development, following guidance provided by the Alberta Woodland Caribou Recovery Plan, as qualified by the Minister of ...